CLAUDIO PTOLOMEO Y LOS MODOS MUSICALES GRIEGOS - Redondo Reyes, Pedro (Myrtia, 2003)
One of the most difficult and important topic in greek harmonics is the musical scale. In the last authors as Cleonides the scales are intended as "tonality", but the alexandrian astronomer Claudius Ptolemy designed a modal system. The thirteen aristoxenian scales are reduced to the ancient seven octave species, since the first aim of Ptolemy's Harmonics is the correspondence of musical theory with instrumental practice.